RHEOLOGICAL INVESTIGATION OF NYSTATIN LOADED LIPOSOMAL GEL FOR TOPICAL APPLICATION: FACTORIAL DESIGN APPROACH - SACHIN S. SALUNKHE; NEELA M. BHATIA; MANISH S. BHATIA (International Journal of Pharma and Bio Sciences, 2013)
Liposomal carriers, eminent for their potential in topical drug delivery have been chosen to help embedding of nystatin molecules in the skin layers. The objective of present study was to develop and carry out rheological investigations of nystatin liposomal gel by using optimization technology in terms of 23 factorial design. In this study attempts have been made to formulate liposomal dispersions and gel formulations by ethanol injection method for topical drug delivery. Present model demonstrates the significance of factors on responses in the liposomal gel formulation. Gels containing liposomes (optimized batch) were prepared in Carbopol® 934 NF and were characterized for rheology, permeation and drug deposition. Factorial design of present study showed that dependent variables are the results of influence of independent variables.The results indicate that the utility of liposomal system as a vehicle for topical delivery of nystatin through the gel is excellent and rational.